Synthesis of 3, 5-dihydroxy-7, 8-dimethoxy-2-(4-methoxyphenyl)benzopyran-4-one derivatives as anticancer agents. Issue 21 (1st November 2016) - Singh, Sarita; Ahmad, Ateeque; Raghuvanshi, Dushyant Singh; Hasanain, Mohammad; Agarwal, Karishma; Dubey, Vijaya; Fatima, Kaniz; Alam, Sarfaraz; Sarkar, Jayanta; Luqman, Suaib; Khan, Feroz; Tandon, Sudeep; et al.
Graphical abstract: Abstract: Different alkyl amide (15a –l ) and alkyl amine (16a –e ) derivatives of 7, 8-dimethoxy-3-hydroxy-2-(4-methoxyphenyl)benzopyran-4-one were synthesized and evaluated for their anticancer activity against five different cancer cell lines using SRB assay. Compounds15e, 15i, 15j and16a –e showed significant anticancer activity within the range of IC50 2.58–34.86 μM. The most promising molecule, 16c, was further analyzed for its effect on cell cycle and apoptosis of estrogen receptor positive cancer cells (MCF-7 cells) which showed that16c triggered apoptosis in MCF-7 cells and arrested cells population at sub-G0 (apoptotic) and G2 M phase. In tubulin polymerization assay, 16c interfered with kinetics of tubulin polymerization.